Las cartas y diarios de Guatemala de Andrzej Bobkowski como ejemplos de traducción intercultural. Propuesta de un nuevo enfoque traductológico - Kasperska, Iwona (Studia Romanica Posnaniensia, 2010)
The aim of this paper is to introduce a new approach in translation studies which is an intercultural translation. Based on the methodology of postcolonial theory, the manipulation school and polysystem theory, it allows for an analysis of texts originally written in the language of the target culture. Application of this new framework is exemplified by diaries and letters of a Polish writer, Andrzej Bobkowski.